Laser microspot welding in electronics production - Mys, I.; Schmidt, Michael (Advances in Laser Materials Processing, 2010)
Aluminium has more significance in electrical and electronic applications such as solar energy collectors or light-weight electric motors and actuators. It combines comparably good thermal and electrical properties with an attractive price and low material weight. however, the main difficulty for a widespread use of aluminium is the lack of a reliable joining process to connect it with copper. the problems during welding of copper and aluminium are caused by a large misalignment in physical properties and even more a poor metallurgical affinity of both materials and therefore high crack sensitivity and formation of brittle intermetallic phases during fusion welding. In this chapter we introduce current results on laser microspot welding of copper and aluminium with the objective to improve the mechanical properties of welded joints. The experiments are carried out on two main welding assemblies - overlap joint with side face weld and overlap joint with fillet weld. Weld microstructure and weld quality are affected by means of two strategies. Firstly, a weight proportion of copper and aluminium in weld microstructure is adjusted and controlled by laser beam incidence position/beam offset and beam incidence angle (for fillet weld). Secondly, an alloying effect of small amounts of silver, nickel and tin filler materials on ductility of weld microstructure has been investigated. the reliability of welded joints is verified by means of dynamic fatigue tests, heat ageing at different temperature profiles and chemical ageing with some selected chemical agents. © 2010 Woodhead Publishing Limited All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Aluminium; Copper; Dissimilar metals; Laser micro joining; Laser micro welding